SYNAPTONEMAL COMPLEX-ANALYSIS IN GOATS CARRYING THE 5/15 ROBERTSONIAN TRANSLOCATION - Amaral, MEJ; Jorge, W. (Elsevier B.V., 1994)
Synaptonemal complexes were analysed by electron microscopy in 2 bucks heterozygous for the 5/15 Robertsonian translocation. The cis configuration (free homologous 5 and 15 chromosomes on the same side of the 5/15 translocated chromosome) was found in all 50 cells examined. This feature is considered a prerequisite for the development of balanced gametes. No association between the sex bivalent and trivalent was observed.
Keywords: MEIOSIS; SYNAPTONEMAL COMPLEX; TRIVALENT; ROBERTSONIAN TRANSLOCATION; GOAT